Performance of various grapes cultivars under agro-climatic conditions of Central Punjab, Pakistan - Bahksh, Allah; Riaz, Sitwat; Kanwal, M. Amna Jamil; Nasir, Maryam; Abbas, Malik Mohsin; Hameed, Aamir; Mahreen, Nida; Aziz, Muhammad Maaz (Journal of Pure and Applied Agriculture, 2023)
Grapes are a rich source of sugars, vitamins, minerals and organic acids which are an important part of human nutrition and vital for growth and development. Climate plays an important role in berry development, growth, fruit ripening and physical as well as biochemical properties of the berry fruits such as size, colour, sugars and taste. Grapes are an important crop that have been grown throughout the world. In Pakistan it is mostly grown in Balochistan and temperate areas. The performance of grapes under climatic conditions of central Punjab are still unexplored. Hence, the experiment was designed to study the performance of nine cultivars of grapes viz., White Seedless, Pearlette, Badana, Black Seedless, Haita, Flame Seedless, King‟s Ruby, NARC black, Cardinal under agro-climatic conditions of Central Punjab during the year 2019-20. Results showed that higher bunch size (307.3 cm), bunch weight (456.2g), berry size (176.8mm), and berry weight (3.82g) was observed in King‟s ruby compared to other varieties. TSS (21.8 ⁰ Brix), TSS: TA ratio (90.9) was higher in white seedless and maximum TA (0.46%) was found in Flame seedless. Vitamin C content was higher in pearlette (26.9 mg /100 g) and NARC Black (27.3 mg/100 g). It is concluded that the performance of King‟s ruby and NARC Black were better in central Punjab condition as compared to other cultivars grown as they have more berry weight and better fruit quality